Approximation theory in up-algebras based on intuitionistic fuzzy sets - P. Jayaramam,; Sudha Dhandapani Subramanian, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper discusses the upper and lower approximations of Atanassov intuitionistic fuzzy sets in crisp and fuzzy approximation spaces in which both constructive and axiomatic approaches are used. In the constructive approach, concepts of intuitionistic fuzzy sets are defined, properties of intuitionistic fuzzy approximation operators are examined. Different classes of intuitionistic fuzzy set algebras are obtained from different types of fuzzy relations. In the axiomatic approach, an operator-oriented characterization of intuitionistic fuzzy sets is proposed.